Comparison of the efficacy of intravitreal ranibizumab for choroidal neovascularization due to pathological myopia with and without a dome-shaped macula. Issue 50 (December 2017) - Cai, Bincui; Yang, Jin; Li, Shuang; Wang, Linni; Chen, Lu; Li, Xiaorong; Li, Zhiqing
Abstract : Abstract: Ranibizumab injection in the treatment of choroidal neovascularization (CNV) secondary to pathologic myopia (PM) with and without a dome-shaped macula (DSM). Prospective observational study. A total of 24 patients (24 eyes) with angiographic evidence of CNV secondary to PM were divided into 2 groups: eyes with a DSM and eyes without DSM. All patients received a baseline intravitreal ranibizumab injection. Additional injections were considered at each follow-up visit. Best-corrected visual acuity (BCVA) and optical coherence tomography were tested monthly through 12 months of follow-up. The mean changes in BCVA, central retinal thickness (CRT, including retinal and CNV thickness), and the number of injections were evaluated. There were no significant differences in visual outcomes between the groups over 12 months ( P  > .05). Patients with a DSM had a mean change in BCVA of +8.7 letters compared with +14.2 letters in patients without a DSM ( P = .68). However, there were more patients without a DSM who gained at least 15 letters from baseline compared with patients with a DSM. By the end of the follow-up, there was no significant difference in the mean change in baseline CRT between patients with and without a DSM (−65.0 and −90.7, respectively, P  = .42). The mean number of injections was 8.83 in the patients with DSM and 8.17 in the patients without a DSM ( P  > .05). For the pathological myopia patients who had CNV with a DSM, the DSM did not alter the effect of the ranibizumab treatment. There was no difference in the visual improvement, anatomic benefit and number of treatments between the 2 groups.